2021
DOI: 10.3390/polym13020209
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Characteristics of Woven Flax/Epoxy Laminated Composite Plate

Abstract: Due to the growing environmental awareness, the development of sustainable green composites is in high demand in composite industries, mainly in the automotive, aircraft, construction and marine applications. This work was an attempt to experimentally and numerically investigate the dynamic characteristics of Woven Flax/Bio epoxy laminated composite plates. In addition, the optimisation study on the dynamic behaviours of the Woven Flax/Bio epoxy composite plate is carried out using the response surface methodo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 24 publications
3
7
0
Order By: Relevance
“…From the figure 1-3 and table 3-5, it can be considered that the fiber orientation and length of the composite may have a relation with each other. As the length increases, the natural frequency is maximum for the #1 orientation than other orientations at higher modes, too which is similar to the result obtained by [25].…”
Section: Modesupporting
confidence: 87%
See 1 more Smart Citation
“…From the figure 1-3 and table 3-5, it can be considered that the fiber orientation and length of the composite may have a relation with each other. As the length increases, the natural frequency is maximum for the #1 orientation than other orientations at higher modes, too which is similar to the result obtained by [25].…”
Section: Modesupporting
confidence: 87%
“…Capasso et al [24] modelled the fiber composite material with solid and shell elements respectively to investigate the structural intensity of the composite material. Gopalan et al [25] investigated effect of stacking sequences on composite numerically and experimentally and found that the natural frequency is more for 0 0 fiber orientations compared to other orientations irrespective of the boundary conditions for out of plane vibrations. Motivated by the information, an attempt is made to conduct a numerical study to understand the effects of fibre orientations and variation in longitudinal parameter on the vibrational characteristics of multilayer composite plate.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, by comparing Young's bending modules to those of traction in the diagram in Figure 9, we find that although the composite is more resistant in bending it is stiffer in traction. This same phenomenon is observed on the woven composite of Flax-epoxy fiber [52]. Moreover, the aforementioned works have applied in the fields of boating, automotive and aeronautics.…”
Section: Traction and Bending Of The Compositesupporting
confidence: 72%
“…Arefi et al [22] presented the size-dependent deflection analysis of FG-CNTRC micro-plates by applying the third-order shear deformation theory to the principle of virtual work. Gopalan et al [23] attempted to experimentally and numerically investigate the dynamic characteristics of flax/bio epoxy functionally laminated composite plates and performed an optimization study using the response surface method (RSM). Cheshmeh et al [24] investigated the buckling and free vibration of FG-CNTRC rectangular plates using the higher-order shear deformation theory.…”
Section: Introductionmentioning
confidence: 99%